Comparison of Corresponding Scores From the Cleft Hearing Appearance and Speech Questionnaire (CHASQ) and CLEFT-Q in Swedish Patients With Cleft Lip and/or Palate. (June 2021) - Stiernman, Mia; Klintö, Kristina; Persson, Martin; Becker, Magnus
Objective: The primary aim of this study was to compare corresponding scores between 2 existing cleft-specific patient-reported outcome measures (PROMs)—Cleft Hearing Appearance and Speech Questionnaire (CHASQ) and CLEFT-Q. The second aim of the study was to investigate patient opinion on the 2 PROMs. Design: Cross-sectional questionnaire study. Setting: Participants were recruited from a University Hospital. They answered CHASQ and CLEFT-Q either in the hospital or at home. Participants: Thirty-three participants with cleft lip and/or palate, aged 10 to 19 years. Main Outcome Measure: CHASQ and CLEFT-Q. Results: The CHASQ scores and the corresponding CLEFT-Q scores on appearance correlated significantly. Corresponding scores regarding speech did not correlate significantly. A majority, 15 (58%) participants, answered that they liked CLEFT-Q more than CHASQ, 18 participants (69%) thought CHASQ was easier to complete, and 19 (76%) thought CLEFT-Q would better inform health care professionals. Conclusion: Both instruments showed strengths and limitations. Clinicians will have to consider each instrument's respective qualities when choosing to implement either PROM.